Determination Of 2-Pyrone-4, 6-Decarboxylic Acid Precurors From Oil Palm Tree Using Different Extraction Process - Saary, Nur Syahirah (2011)
The precursors of 2-pyrone-4,6-dicarboxylic acid (PDC) were investigated from selected oil palm cultivars in Malaysia. The studied cultivars include Dura x Pisifera (Dura x URT), Dura x Tenera, Deli dura x AVROS, Dumpy x Yangambi x AVROS, Deli dura x yangambi, Deli dura x Pisifera x H&C. All samples were divided into 11 parts; outer bark, trunk (inner part), frond (rachis and petiole), leaves, fruits (flesh, albumen and kernel shell) and empty fruit bunch (EFB fiber, midrib spine leaflets and stalk of fruit bunch). Subcritical water extraction and alkaline subcritical water extraction were chosen to investigate the optimum conditions to produce PDC precursors. Oil palm trunk powder (inner part) was used in both extractions to find the optimum condition of PDC precursors. Three parameters were used for subcritical water extraction that includes temperatures, times and volumes of water. For alkaline subcritical water extraction four parameters were used which were concentrations, temperatures, times and volume of sodium hydroxide (NaOH) solutions. The results indicated that, optimum condition for subcritical water extraction was at 200°C, 40-60 min and 100 ml. While for alkaline subcritical water extraction showed the best presence of PDC precursors at 0.1M, 180°C, 20 min and 100 ml of NaOH solvent. From the results Dura x Pisifera (Dura x URT) showed high total yield of PDC precursors of 8.40%. While trunk (inner part) and kernel shell consisted high yield of total PDC precursors. Results obtained from high performance liquid chromatography (HPLC) and confirmed by nuclear magnetic resonance (NMR) showed that the ρ-hydroxybenzoic acid was the main precursor of PDC in the oil palm biomass.